2009
DOI: 10.1073/pnas.0813172106
|View full text |Cite
|
Sign up to set email alerts
|

Human HA and polymerase subunit PB2 proteins confer transmission of an avian influenza virus through the air

Abstract: The influenza virus genes that confer efficient transmission of epidemic and pandemic strains in humans have not been identified. The rapid spread and severe disease caused by the 1918 influenza pandemic virus makes it an ideal virus to study the transmissibility of potentially pandemic influenza strains. Here, we used a series of human 1918-avian H1N1 influenza reassortant viruses to identify the genetic determinants that govern airborne transmission of avian influenza viruses. We have demonstrated that the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
222
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(234 citation statements)
references
References 37 publications
11
222
1
Order By: Relevance
“…The ferret model recapitulates the efficient transmission of seasonal influenza viruses and the poor transmission of avian influenza viruses in humans (25,(29)(30)(31). The transmission kinetics and efficient RD transmission of the 2010 and 2011 A(H3N2)v viruses is comparable to that observed with seasonal influenza viruses in ferrets (23,29,32,33).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The ferret model recapitulates the efficient transmission of seasonal influenza viruses and the poor transmission of avian influenza viruses in humans (25,(29)(30)(31). The transmission kinetics and efficient RD transmission of the 2010 and 2011 A(H3N2)v viruses is comparable to that observed with seasonal influenza viruses in ferrets (23,29,32,33).…”
Section: Discussionmentioning
confidence: 72%
“…Human-adapted seasonal influenza H1 and H3 HA demonstrate high specificity for α2-6-sialylated glycans, and it has been postulated that efficient and sustained human-to-human transmission of influenza viruses requires an α2,6 sialic acid receptor-binding preference (21,22,27,30,32,41). Bateman et al demonstrated that TRS H3N2 viruses isolated in the late 1990s bound exclusively to α2-6-sialylated glycans (42).…”
Section: Discussionmentioning
confidence: 99%
“…4F and when comparing the viral titers and length of shedding in respiratory droplet contacts from RCP10 and 2RCP10:6M98. The internal genes have been implicated in transmission not only within avian species (20)(21)(22) but also from avian to mammalian species (23,24). A complete set of viruses tested and their transmission phenotype are listed (Table 4 and supporting information (SI) Fig.…”
Section: Adaptive Mutations On Rcp10 Surface Proteins Support Respiramentioning
confidence: 99%
“…The PB2 subunit interacts with PA in the cytoplasm initially and is subsequently transported as a dimer into the nucleus [10]. The viral RNA polymerase complex is important for the efficient propagation of the virus in the host and for its adaptation to new hosts [11], and considered as a major determinant of the pathogenicity of the 1918 pandemic virus [12]. The mutations in PB2 protein can affect the virulence of influenza A virus [13], change RNA binding activity [14,15], and contribute to intra-and inter-host transmission in diverse virus backgrounds [15,16].…”
Section: Introductionmentioning
confidence: 99%